Application of Invasive Plants as Biochar Precursors in the Field of Environment and Energy Storage - Yang, Lei; Deng, Yuanyuan; Shu, Zihan; Chen, Qiang; Yang, Hailan; Tan, Xiaofei (Frontiers in Environmental Science, 2022)
Plant invasion caused due to various human activities has become a serious problem affecting ecosystem diversity and imposes a burden on the economy. In recent years, there have been increasing studies on the application of biochar (BC) in the field of environmental protection. Invasive plants, which are considered as a kind of hazardous waste biomass, can be used as feedstocks to prepare BC. Consumption of invasive plants for BC preparation can achieve a win-win situation in ecology and resources. This can solve a series of ecological problems caused by invasive plants to a certain extent while also realizing the resource utilization of wastes and bringing considerable economic benefits. Based on previous studies, this paper summarizes the progress of preparing and using invasive plant biochar (IPB). This includes the production, modification, merit and demerit of IPB, its application in improving soil quality, the adsorption of pollutants, application in energy storage, and climate change mitigation potential. It provides a basis for further study of IPB based on the currently existing problems and proposes a direction for future development.